ANALYSIS OF ILLUSTRATION STYLES WITH POSITIVE EFFECTS ON SOCIAL MEDIA ON THE MENTAL HEALTH OF GENERATION Z - Lisa Indriati; Agnestasia Esther Ewitrawati (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2025)
Generation Z is one of the most active social media user groups and is often exposed to various visual content, both positive and negative. Exposure to negative visual content can affect mental health, leading to fatigue, stress, and reduced focus. However, Generation Z also engages with positive content that’s entertaining and educational. One form is illustration, where the visual style influences their emotional experience. This study aims to analyze illustration styles that positively impact Generation Z’s mental health when consuming social media content and to examine the relationship between their style preferences and these positive effects. Data were collected using a mixed-method approach, combining literature review and a survey of 34 respondents aged 18–22 years. The results show that cartoon and hand-drawn illustration styles that are simple, humorous, and visually pleasant are the main preferences of Generation Z, as they convey authenticity and emotional expression. Supporting elements such as pastel, warm, and earthy color palettes; rounded, expressive character designs; and handwritten typefaces enhance these positive effects. The study concludes that the right illustration style, supported by appropriate visual elements, can promote calmness, entertainment, and motivation, contributing positively to Generation Z’s mental well-being on social media.